THE IMPACT OF INDOMARET OPERATED ON TRADITIONAL SMALL KIOSKS SALES IN MANADO CITY - Achmad, Sandy (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Competition between traditional retail and modern retail has most attention, because it puts one party (the traditional retail) in a weak position. The rapid growth of modern markets begun since the Indonesian government promulgated the presidential decree in 1998 that removed the retail business from the foreign investment negative list (Pandin in Tumbuan and Shiratake, 2010). Furthermore, in 2000, under the liberalization policy, the Indonesian government again promulgated another presidential decree to open the local retailing industry to the modern markets run by foreign capitals. These policies have led to fierce competition in this industry all over the country. The objects of this research are the small kiosks near and parallel to Indomaret in Manado city, especially in Malalayang sub-district. This research purpose for analyze how much an impact of opened Indomaret on the sales of existing small kiosks. This research is using qualitative method to describe the topic and the result of research. The research result show more than 60% of informant in this research got negative impact on their sales. Government of Manado city is should be to give more attention to small kiosk (traditional retail). For example, through the structured trainings, business guidance, help the business capital, and legal protection through Local Regulation, so small kiosks have more protected and being able to compete. Keywords: marketing, marketing channels, retailer, sales